The twistor string: a new framework to study Yang-Mills theories, and its spacetime formulation - Bandos, I.A.; de Azcárraga, J.A.; Miquel-España, C. (Вопросы атомной науки и техники, 2007)
We give a brief review of the twistor string approach to supersymmetric Yang-Mills theories with an emphasis on the different formulations of (super)string models in supertwistor space and their superspace form. We discuss the classical equivalence among the Siegel closed twistor string action and the Lorentz harmonics formulation of the (N=4) tensionless superstring, and notice the possible relation of the twistor string to the (D=10) Green-Schwarz superstring action, as well as to models in the enlarged, tensorial superspaces that are relevant in higher spin theories. Представлено короткий огляд так званого підходу твісторної струни до дослідження суперсиметричних теорій Янга-Міллса. Особлива увага приділяється різним формулюванням моделей (супер)струн у просторі супертвісторів й їхній суперпросторовій формі. Ми обговорюємо класичну еквівалентність дії твісторної струни у формі Зігеля й Лоренц-гармонійного формулювання (N=4) суперструни без натягу (нуль суперструни), а також відзначаємо можливий зв'язок твісторної струни з десятивимірною суперструною Гріна-Шварца й з моделями в розширеному суперпросторі, що використовувалося раніше для опису вищих спінів. Представлен краткий обзор так называемого подхода твисторной струны к исследованию суперсимметричных теорий Янга-Миллса. Особое внимание уделяется различным формулировкам моделей (супер)струн в пространстве супертвисторов и их суперпространственной форме. Мы обсуждаем классическую эквивалентность действия твисторной струны в форме Зигеля и Лоренц-гармонической формулировки (N=4) суперструны без натяжения (нуль суперструны), а также отмечаем возможную связь твисторной струны с десятимерной суперструной Грина-Шварца и с моделями в расширенном суперпространстве, которое использовалось ранее для описания высших спинов.